(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present investigation is to find out the difference in the Social Attitude among Tribal students of higher secondary school in North Gujarat. The total sample consisted of 360 students. Out of which 180 were boys students and 180 were girls students. For this purpose of investigation Social Attitude Scale” (1995) by Prof. Dr. A.S.Patel, Dr. Navin Patel & Dr. Dinesh Panchal was used. The obtained data were analyzed using t test to know the Mean difference between boys students and girls students. The results show that there is a significant difference between the Mean score of boys students and girls students of Higher Secondary school in relation to Women Status, Family Planning and Sex Education